New Directions in the Philosophy of Technology
IX, 225 p.
Keywords: In this collection we finally find the philosophy of technology, a young and rapidly developing area of scholarly interest, making contact with history of science and technology, and mainstream epistemological and metaphysical issues. The sophistication of these papers indicates the maturity of the field as it moves away from the advocacy of anti-technology ideological posturing toward a deeper understanding of the options and restraints technological developments provide. The papers presented here take us over a threshold into the real world of complicated social and technological interactions where science and art are shown to be integral to our understanding of technological change, and technological innovations are seen as configuring our knowledge of the world and opening up new possibilities for human development. With its rich historical base, this volume will be of interest to all students concerned about the interactions among technology, society, and philosophy.